Vaccination and therapeutic strategies against M. tuberculosis in the guinea pig model - Eckhardt, Emmelie Margarete; Justus Liebig University Giessen (My University, 2023)
Human tuberculosis is caused by bacteria of the Mycobacterium tuberculosis complex, mainly by Mycobacterium tuberculosis (Mtb) itself. Mtb causes numerous infections, illnesses and deaths each year and is the leading cause of death among bacterial pathogens worldwide. In this thesis, two major problems in tuberculosis control and eradication were addressed: the lack of an efficient vaccine against tuberculosis and the increasing emergence of drugresistant Mtb-strains. The main focus has been on the hallmark of tuberculosis-infection, the granuloma, which represents the niche of persistence for mycobacteria but is also important for the development of host immune responses. Guinea pigs were the animal of choice for the studies performed because they are naturally susceptible to Mtb and develop granulomas after infection that are comparable to those of human tuberculosis patients. It was also significant for the first project that guinea pigs have a functional CD1 type 1 system, homologue to those in humans. The avenues of exploration and knowledge about human CD1 type 1 protein function and the resulting T cell responses, have been summarized in a review paper (publication I). In the first project (publication II), it was shown that vaccination with PIM6 induced a PIMspecific, CD1-restricted T-cell response. After infection with virulent Mtb, vaccinated animals showed milder pathology as evidenced by smaller and fewer necrotic granulomas and less bacterial load compared with nonvaccinated guinea pigs. Histological and transcriptomic analyses demonstrated lower proinflammatory cyto- and chemokine levels in protected animals, whereas CD1b expression was pregulated in draining lymph nodes. Overall, this strongly suggests a contribution of PIM-specific T cells to the protection of guinea pigs after vaccination. For the second project (publication III), the efficacy and pharmacokinetics of the new antituberculosis drug BTZ-043 were investigated in the guinea pig. First, a dose-finding study was conducted to determine the appropriate dosage of BTZ-043 in the guinea pig, in which plasma levels of the drug and its metabolite were detectable in plasma for 24 h. Subsequent multidose studies demonstrated that BTZ-043 was detectable in plasma at effective concentrations after multiple applications and also reached BCG-induced granulomas at high concentrations. Finally, treatment with BTZ-043 was shown to reduce pathology and bacterial load in granuloma, draining lymph nodes, and spleen in guinea pigs. In conclusion, the work and results of this dissertation contribute to the research and development of new and innovative methods to control and eradicate tuberculosis.
Keywords: Tuberculosis; Guinea Pig; Vaccination; PIM; CD1; BTZ-043; Animal Model; ddc:000; ddc:500; ddc:570; ddc:590; ddc:610; ddc:630